Applicability of Fourier transform infrared (FTIR) spectroscopy in rapid identification of some Candida and dermatophyte species infections in humans. (23rd June 2016) - Mohammed, Yaser F.; Salem, Elsayed Z.; Shahin, Ibrahim M. I.; Abdo, Hamed M.; Emam, Hanaa E.; Fawzy, Mahmoud; Abdel Salam, Mohamed F.
Abstract: Traditional systems of identifying yeasts and dermatophytes have many disadvantages. Preliminary data on a radically different approach based on optical spectroscopic techniques suggest that these techniques may offer some advantages. We conducted a trial to verify the practical applicability of Fourier transform infrared (FTIR) spectroscopy in the identification of some yeast and dermatophyte species, in which samples from 50 patients with superficial fungal infections were cultured on Sabouraud dextrose agar with chloramphenicol and cycloheximide (actidione) and studied using FTIR microspectroscopy. Spectra of the same species were identical, whereas spectra of different species did not show similarity. This study showed that FTIR microspectroscopy is promising and can be used to obtain, with a single measurement, a "molecular fingerprint" of Candida and dermatophyte species. It can be improved further in terms of reliability.